Vitamin D in skin psoriasis and psoriatic arthritis: where does it stand? - Sarah El Tawab; Marwa E Eldeeb; Yousra H Abdel- Fattahah (Wolters Kluwer Medknow Publications, 2021)
Background Psoriasis can affect skin, as well as articular and extra-articular tissues. It has a multifactorial pathogenesis in which vitamin D has been implicated. Objective To assess vitamin D status in patients with skin psoriasis (PsO) and/or psoriatic arthritis (PsA) and its correlation with disease activity and quality of life (QOL) in a cohort of Egyptian patients. Patients and methods This cross-sectional study included 45 patients, divided into group A (21 patients) with PsO and group B (24 patients) with PsA, as well as 38 healthy controls as group C. Disease activity and QOL were assessed in all patients. The serum total 25-hydroxy vitamin D (25(OH)D) level was measured for all participants. Results The median psoriasis area severity index was 8.4 (0.8-45.8) in group A and 10.9 (0.9-44.4) in group B. The median dermatology life quality index in group A was 7 (2-18) and in group B was 12 (3-30). In group B, the mean disease activity in PsA was 40.2±21.2 and PsAQOL was 14.5±4.18. Serum 25(OH)D levels were not statistically different among the three studies groups (H=4.213 at P=0.122). However, the receiver operating characteristic curve cutoff value (26.8 ng/ml) showed that group C had a statistically higher number of participants with normal vitamin D status compared with groups A and B. Conclusion Although a higher percentage of vitamin D deficiency may be found among patients with PsO and PsA, 25(OH)D levels did not correlate with different parameters in both patient groups.